Microstructure elements affect the mass transfer in foods: The case of convective drying and rehydration of pumpkin - Rojas M.L. (2018)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding the project nº 2016/18052-5; to the National Council for Scientific and Technological Development (CNPq, Brazil) for funding the project nº 401004/2014-7; and to Cienciactiva for the M.L. Rojas Ph.D. scholarship (CONCYTEC, Peru; Contract 087-2016-FONDECYT), from the ‘‘Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica”. The authors are also grateful to the “Laboratório de Análise de Imagens” (LPV-ESALQ/USP) for the support and facilities for X-ray analysis.